METODE JUST IN TIME SEBAGAI UPAYA DALAM MENINGKATKAN EFISIENSI BIAYA PERSEDIAAN BAHANBAKU (Studi Kasus pada PT. Bintang Baru Sentosa) - Neneng Dahtiah; Setiawan Setiawan (Faculty of Economic and Business Universitas STIKUBANK, 2020)
The textile and textile products (TPT) industry in Indonesia still has a lot of problems, one of which is the problem of raw materials which are considered to be unable to compete with the same material from importation sources. This requires the company continue to strive to increase productivity and cost efficiency to mitigate the increase in prices of raw materials charged to consumers. One effort that can be done by the company is to improve the efficiency of the cost of raw material inventory. The company must be able to plan and control the company's raw material inventory to support the effectiveness of its raw material costs. By having good planning and control, the company will avoid the problem of excess and lack of raw material inventory in carrying out production activities. This study aims to determine the application of the Justintime system at PT Bintang Baru Sentosa in increasing the efficiency of the company's raw material inventory costs. The type of research is quantitative qualitative research with a case study approach. Data sources obtained from primary data and secondary data. The methods used in this study include: interviews, observation, and documentation studies.The results of the study show that using Justintime in controlling raw material inventories has cost efficiencies of Rp18.418.185,- for 75/72 F DTY and 150/48 F DTY with a cost efficiency level of 75%. Keyword:Raw Materials, Inventories, Just.intime (JIT), Cost Efficiency